A Study of Academic Leadership Capabilities of Teachers in a Selected No. 2 Basic Education High School in Myanmar - Jacqueline, Mary; Rungrojngarmcharoen, Kanog-on (Scholar: Human Sciences, 2015)
This is a study of academic leadership capabilities perceived by teachers in a selected No.2 Basic Education High School in Myanmar. 45 teachers participated in this school. This study is aimed at determining the expectations from the current academic leadership capabilities demonstrated by the teachers in a selected school. This study is a descriptive study and a survey questionnaire based. To study academic leadership capabilities, this research mainly focuses on three interlocked core elements: personal, interpersonal and cognitive capabilities. The findings show that there were significant academic leadership capabilities that were expected from the teachers, such as maintaining a good work/life balance, keeping things in perspective and being bound by a school’s code of ethics. In contrast, the least significant ones were having an ability to engage their peers in analyzing and using information to strengthen instructors, working constructively with people who are resistors or are over-enthusiastic and willing to take a hard decision. On the other hand, the academic leadership capabilities that the teachers believed that they had were having energy, passion, enthusiasm for learning and teaching, maintaining a good work/life balance and keeping things in perspective, and being bound by a school’s code of ethics while the least ones were willing to take a hard decision, having ability to serve as a mentor for novice teachers, and understanding the curriculum of the subjects that they teach and use them in planning instruction and assessment. Nevertheless, there remain some interesting findings on differences between expected qualities and current academic leadership capabilities practiced by the teachers. In personal capabilities, the highest different level between expected and current personal capabilities was being willing to take a hard decision which differences level is at .98. In interpersonal capabilities, the highest differences between expected and current interpersonal capabilities were having ability to serve as a mentor for novice teachers. The different level was at 1.22. About cognitive capabilities, the highest difference between expected and current capabilities was learning from experiences. The different level was at 1.78. While teachers’ expectation was too high on these capabilities,the capabilities that they perceived currently were the least ones. Taking into account these interesting differences between expected and current academic leadership capabilities perceived by the teachers, a school leader should pay close attention of how to bridge the gap. This study provides fruitful solutions to improve teachers’ leadership capabilities. This study could also be useful for deans, administrators, department heads, principles and head masters who could help enhance academic leadership capabilities of their teachers.